2016
DOI: 10.18632/oncotarget.12793
|View full text |Cite
|
Sign up to set email alerts
|

The somite-secreted factor Maeg promotes zebrafish embryonic angiogenesis

Abstract: MAM and EGF containing gene (MAEG), also called Epidermal Growth Factor-like domain multiple 6 (EGFL6), belongs to the epidermal growth factor repeat superfamily. The role of Maeg in zebrafish angiogenesis remains unclear. It was demonstrated that maeg was dynamically expressed in zebrafish developing somite during a time window encompassing many key steps in embryonic angiogenesis. Maeg loss-of-function embryos showed reduced endothelial cell number and filopodia extensions of intersegmental vessels (ISVs). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 44 publications
(66 reference statements)
3
14
1
Order By: Relevance
“…Blocking the AKT signaling resulted in the attenuated capability of migration obviously in breast carcinoma . More interestingly, EGFL6 stimulates activation of AKT signaling in zebrafish . In our study, we found that p‐AKT was downregulated in the shEGFL6 group (Figure A), which means AKT pathway was inhibited when silence EGFL6 in NPC cells.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Blocking the AKT signaling resulted in the attenuated capability of migration obviously in breast carcinoma . More interestingly, EGFL6 stimulates activation of AKT signaling in zebrafish . In our study, we found that p‐AKT was downregulated in the shEGFL6 group (Figure A), which means AKT pathway was inhibited when silence EGFL6 in NPC cells.…”
Section: Discussionmentioning
confidence: 56%
“…EGFL6 is an epidermal growth factor‐like protein, it is well known that it plays a series of roles in endothelial cell behaviors and angiogenesis of . Recently, there are some reports prove that EGFL6 involved in the progression of human cancer, such as ovarian cancer, breast cancer, meningioma .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the potential mechanisms of EGFL6 in CRC carcinogenesis, most studies have found that EGFL6 acts through the ERK pathway . To the best of our knowledge, this was the first study associating the function of EGFL6 and the Wnt/β‐catenin pathway.…”
Section: Discussionmentioning
confidence: 84%
“… 12 In a zebrafish model, EGFL6 promoted angiogenesis via a mechanism that depended on the RGD domain (Arginyl-glycyl-aspartic acid domain) and on the activation of the Akt and Erk pathways. 18 Loss of EGFL6 decreased the number of endothelial cells and vessels, suggesting that EGFL6 acts as a positive regulator of functional vessel formation. 18 …”
Section: Discussionmentioning
confidence: 98%
“… 18 Loss of EGFL6 decreased the number of endothelial cells and vessels, suggesting that EGFL6 acts as a positive regulator of functional vessel formation. 18 …”
Section: Discussionmentioning
confidence: 98%